Analisa Partisipasi Politik Di Amerika Serikat - Haqqi, Halifa - (Transformasi, 2012)
AbstractPolitical participation is important thing of democratic system. United States of Amerika as â€œfather ofdemocracyâ€ has a lot of kind of political participation such as voting, campaign activity, ParticularizedContacting, Cooperative Activity, and Unconventional Participation. Many factors that influence politicalparticipation, it is make deferences of total political participation in United States of AmericaKey Word: Participation; Political; USA